On certain aspects of the need and possibility for the administrative-territorial reform in Estonia - Raudjärv, Matti (Estonian Discussions on Economic Policy, 2014)
The paper treats important problems of regional and local government policy, such as the possibility of and need for the administrative-territorial reform, including merging of municipalities and definition of mutual relationships between the state and local governments and their functions. The need for sustainable and strong municipalities has been emphasised also on the level of the European Union already several years ago. Possible mergers of Estonian county centres with their surrounding rural municipalities, also the possibility for having several centres of attraction in a county are discussed. Statistics on demographic changes in the Estonian population, concentration of the population above all to larger cities, and decrease in rural population are presented. Also statistics, for instance, on changes in the number of pupils in counties are presented. A few suggestions are made for the further development of the regional and local government policy, including based on the considerably more radical activities in Finland in this field.